Effectiveness of extract Songga wood (Strychnos lucida) towards survival and antibody titers on Tilapia (Oreocromis niloticus) that infected Streptococcus agalactiae - Anis Zubaidah; Sri Samsundari; Vivi Fitriani (Universitas Muhammadiyah Malang, 2019)
Nile Tilapia or Tilapia Fish (Oreochromis niloticus) is one of commodity with a high number of consumers. But, Streptococcus agalactiae attack caused a decline in production. One way to reduce these diseases by using natural materials of songga wood (Strychnos lucida R.Br) where the songga wood contains many compounds like alkaloid, phenols, flavonoids, triterpenoids, which can inhibit bacterial growth by damaged cell membrane. The results showed that the inhibitory songga wood extract against Streptococcus agalactiae was highly significant, and shows with the highest survival rate of 90% and proved by theincreasingantibodytitersafteraddingsonggawood extract.